Images and stories from the borderlands - Meinhof, Ulrike (Nordlit, 2014)
My paper introduces geo-political and symbolic dynamics of 21st century Europe through three conceptual prisms: those of borders or border communities, networks, and neighbourhoods. Each of these can be seen as both descriptive lenses for capturing specific phenomenon of social interaction in geographical spaces as well as metaphors for imagining human encounters across visible or invisible divisions, such as for example nationhood, ethnicity, race, religion or gender. In the first part, my paper analyses the implications for each of these imaginaries for theoretical and empirical research. In the second part I will show with different examples how these conceptual frames affected my own fieldwork practices in a series of European research projects during the last decade: European Border Discourse, 2000-2003; Changing City Spaces 2002-2005, Sefone 2007-2010 and TNMundi 2006-2010. Examples will include a rich, multi-layered spectrum of every-day life narratives as well as examples of artistic productions. A version of this paper with the text of interviews in both German and English throughout is available on request from the author.